The determinants of leverage decisions: Evidence from Asian emerging markets - Quratulain Zafar; Winai Wongsurawat; David Camino (Cogent Economics & Finance, 2019)
This study provides a stage-level analysis of firm-scale pooled data of 16 Asian countries to classified income economy-based data for various firm- and country-specific predictors of leverage. Our analysis captures the selection impact of both micro- and macro-level determinants on capital structure with and without income economy-based models. The regression model evaluated the significance of predictor variables based on random effect model of panel data setting. The study further explores the issue of interest by looking at key individual regression models by income economy to avoid any potential loss of information. We argue that this approach provides a comprehensive and insightful set of determinants because of the newer dimension of income economy classification based on per-capita Gross National Product (GNP) defined by the World Bank. The estimating equations for financing determinants identify the additional variables of non-debt tax shield, liquidity, tax and GDP growth rate in case of Asian countries. Our study establishes that the core variables of tangibility, growth, size, and profitability retain their significance for leverage choice in both options during 2008-2014 in Asian economies. Furthermore, the findings show that the financing choices of firms in Asian regional markets are complemented by financial system development stages using the equity market, the bond market and the banking industry as proies.
Keywords: G30; G20; F61; F62; C33; 330; firm-specific determinants; country-specific determinants; income economies; Asian countries